Quality of life and deglutition after total laryngectomy - Pernambuco, Leandro de Araújo; Oliveira, Jabson Herber Profiro de; Régis, Renata Milena Freitas Lima; Lima, Leilane Maria de; Araújo, Ana Maria Bezerra de; Balata, Patrícia Maria Mendes; Cunha, Daniele Andrade da; Silva, Hilton Justino da (International Archives of Otorhinolaryngology, 2012)
Introduction: Total laryngectomy creates deglutition disorders and causes a decrease in quality of lifeAim: To describe the impact of swallowing and quality of life of patients after total laryngectomy.Method: A case series study. Patients completed a Swallowing and Quality of Life questionnaire composed of 44 questions assessing 11 domains related to quality of life (burden, eating duration, eating desire, frequency of symptoms, food selection, communication, fear, mental health, social functioning, sleep, and fatigue). The analysis was performed using descriptive statistics, including measures of central tendency and variability.Results: The sample comprised 15 patients who underwent total laryngectomy and adjuvant radiotherapy. Of these, 66.7% classified their health as good and 73% reported no restrictions on food consistency. The domains “communication” and “fear” represented severe impact and “eating duration” represented moderate impact on quality of life. The items with lower scores were: longer time to eat than others (domain “eating duration”), cough and cough to remove the liquid or food of the mouth when they are stopped (domain “symptom frequency”), difficulties in understanding (domain “communication”) and fear of choking and having pneumonia (domain “fear”).Conclusion: After total laryngectomy, patients report that swallowing issues have moderate to severe impact in “communication,” “fear,” and “eating duration” domains.
Keywords: quality of life; laryngeal neoplasms; laryngectomy; deglutition; deglutition disorders